Two Cases of Chronic Myeloid Leukemia in Lymphoid Blast Phase Presented as Philadelphia-Positive Acute Lymphoblastic Leukemia - Tae Hoon Lee; Hee Young Ju; Ji Won Lee; Ki Woong Sung; Keon Hee Yoo (The Korean Society of Pediatric Hematology-Oncology, 2023)
Patients with chronic myeloid leukemia (CML) in lymphoid blast phase can present clinical characteristics resembling Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph+ ALL). It is crucial to distinguish between two diseases since their treatments differ. We present two cases of children who presented with CML lymphoid blast crisis, who were initially difficult to distinguish from Ph+ ALL.